A colorful photonic crystal film structure capable of repeated electrochromic change and a preparation method thereof

By introducing the inner support structure of inorganic oxide hollow nano microspheres into the electrochromic film and combining the inverse opal electrochromic material to form a composite photonic crystal film, the problem of deformation of the film during the heat treatment in the prior art affects the photonic crystal structure, and achieving high-quality colorful output and repeatable discoloration are achieved.

CN116449621BActive Publication Date: 2025-04-29DALIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310352795.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-04
Publication Date
2025-04-29
Estimated Expiration
2043-04-04

AI Technical Summary

Technical Problem

The existing transition metal oxide colorful electrochromic films lack internal support during heat treatment, resulting in deformation affecting the photonic crystal structure, and the chromogenic quality needs to be improved.

Method used

The opal photonic crystal structure composed of inorganic oxide hollow nanomicrospheres is used as the support framework, and the inverse opal structure electrochromic material is filled in its gaps to form a photonic crystal film composited by hollow nanomicrospheres-electrochromic material. By changing the thickness of the hollow nanomicrosphere shell and the direction of the applied electric field, colorful output and repeatable discoloration are achieved.

Benefits of technology

It improves the color quality and micromorphology of the film, achieves rapid response and repeatable electrochromic, rich in color and stable discoloration effect, and has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004162222160000011
    Figure HDA0004162222160000011
  • Figure HDA0004162222160000012
    Figure HDA0004162222160000012
  • Figure HDA0004162222160000013
    Figure HDA0004162222160000013
Patent Text Reader

Abstract

The present invention discloses a colorful photonic crystal film structure capable of repeated electrochromic change and a preparation method thereof, and belongs to the field of preparation of electrochromic photonic crystal materials. A fast-response electrochromic material is combined with an inorganic oxide hollow nano-microsphere photonic crystal material, and the adjustable shell thickness of the hollow nano-microsphere is used to enrich the types of structural colors of the electrochromic photonic crystal, and the color can be cyclically changed by changing the bias direction. The composite photonic crystal structure electrochromic film has a wide color range and high color quality, and has great application value as an electric response color development material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a colorful photonic crystal film structure capable of repeated electrochromic change and a preparation method thereof, and belongs to the field of preparation of electrochromic photonic crystal materials. Background Art

[0002] Electrochromic phenomenon refers to the reversible change phenomenon that the optical properties of the material change by causing an electrochemical redox reaction in the electrochromic material through an external electric field. Transition metal oxides will generate polarons under the action of an external electric field to undergo electrochemical redox reactions, so most transition metal oxides and their derivatives have electrochromic properties. Studies have found that when transition metal oxide electrochromic materials undergo electrochemical redox reactions, they are accompanied by changes in refractive index, reflectivity or transmittance, and when the electrochromic material has a mesoporous structure, as the specific surface area increases, the ion diffusion coefficient increases, which can also accelerate the electrochromic response speed and improve the coloring efficiency. Therefore, the preparation of electrochromic porous films with intact morphology and bright color is of great research significance for further research.

[0003] At present, in the research of transition metal oxide colorful electrochromic films, most of the film structures are usually inverse opal photonic crystal structures that have been heat-treated at a uniform rate of temperature increase (see Kuai SL, Bader G, Ashrit PV. Tunable electrochromic photonic crystals [J]. Applied Physics Letters, 2005, 86 (22), Hui-Ying Qu, Junxin Wang, Jose Montero, Yao Li and Gunnar A. Niklasson. Mu Multicolored absorbing nickel oxide films based on anodic electrochromism and structural coloration [J] Applied Physics Letters, 2021, 129 (123)), and their color-producing types have been further studied. However, the above method has a great influence on the photonic crystal structure due to the shrinkage deformation of the porous film without internal support during the heat treatment process, and its color-producing quality needs to be improved. Introducing an internal support structure into the above structure to reduce the degree of thermal deformation is an effective solution to the above problem. However, there has been no research report on this type of photonic crystal structure electrochromic film with an internal support structure. Summary of the invention

[0004] The purpose of the present invention is to provide a colorful photonic crystal film structure and a preparation method thereof that can achieve fast response and repeatable electrochromism by applying a voltage bias. The fast-response electrochromic material is combined with the inorganic oxide hollow nano-microsphere photonic crystal material, and the adjustable shell thickness of the hollow nano-microsphere is used to enrich the structural color types of the electrochromic photonic crystal, and the color can be cyclically changed by changing the bias direction. The composite photonic crystal structure electrochromic film has a wide color range and high color quality, and has great application value as an electric response color development material.

[0005] A colorful photonic crystal film structure with repeatable electrochromic properties is an opal photonic crystal structure supporting skeleton (H-inorganic oxide PCs) composed of hollow nano-microspheres of inorganic oxides, and an inverse opal structure electrochromic material (electrochromic material IOPCs) filled in the gaps of the skeleton, forming a hollow nano-microsphere-electrochromic material composite photonic crystal film (H-inorganic oxide / electrochromic material PCs), that is, the hollow nano-microspheres are embedded in the holes of the inverse opal structure electrochromic material. Among them, the micro-nano structure of the film is a tightly packed multi-cavity structure; the hollow inorganic oxide nano-microspheres have an air core-inorganic oxide shell structure, the microsphere diameter is 200-400nm, and the inorganic oxide sphere shell layer thickness is between 5-60nm. The reflection peak of the film can be electrically driven to shift, and the photonic crystal structure is regulated by changing the thickness of the hollow nano-microsphere shell, and the colorful output of the electrochromic photonic crystal can be achieved by combining the electrochromic properties of the material.

[0006] According to the above technical solution, preferably, the shell material of the inorganic oxide hollow nano-microspheres constituting the supporting skeleton is one or two of SiO2, MnO2, and ZrO2.

[0007] According to the above technical solution, in a preferred case, the volume ratio of the electrochromic material in the thin film structure is 26%, and the volume ratio of the hollow nano-microspheres in the thin film structure is 74%.

[0008] According to the above technical solution, preferably, the inorganic oxide hollow nano-microspheres are formed by removing the polymer core microspheres by the heat treatment step after the inorganic oxide shell layer covers the polymer core microspheres.

[0009] According to the above technical solution, in a preferred case, the polymer core is one of polystyrene, polymethyl methacrylate, and poly(styrene-methyl methacrylate-acrylic acid), and the inorganic oxide shell is one or more of SiO2, MnO2, and ZrO2.

[0010] According to the above technical solution, preferably, the particle size of the polymer core of the polymer core-inorganic oxide shell structured nanospheres is in the range of 200-400 nm, preferably 240±5 nm.

[0011] According to the above technical solution, preferably, the thickness of the inorganic oxide shell layer of the polymer core-inorganic oxide shell structured nanoparticles is 5-60 nm.

[0012] According to the above technical solution, in a preferred case, the electrochromic material is one of WO3, V2O5, and NiO; the colorful photonic crystal thin film material that can repeatedly change electrochromism is one or more of H-SiO2 / WO3, H-SiO2 / V2O5, H-SiO2 / NiO, H-MnO2 / WO3, H-MnO2 / V2O5, H-MnO2 / NiO, H-ZrO2 / WO3, H-ZrO2 / V2O5, and H-ZrO2 / NiO.

[0013] The repeatable electrochromic photonic crystal structure film provided by the present invention has a cyclic response capability (number of cycles>100 times).

[0014] The color of the repeatable electrochromic photonic crystal structure film provided by the present invention can be adjusted by changing the thickness of the inorganic oxide shell layer, such as blue, green, yellow, and red.

[0015] The repeatable electrochromic photonic crystal structure film of the present invention can realize electrochromic change by means of an external electric field, such as blue-purple change, green-cyan change, yellow-green change, cyan-blue change, red-green change, and red-orange change.

[0016] The present invention also provides a method for preparing the above-mentioned repeatable electrochromic photonic crystal structure film, comprising the following steps:

[0017] 1) constructing an opal photonic crystal composed of inorganic oxide-coated polymer microspheres on a conductive substrate as a precursor template of a hollow nano-microsphere photonic crystal, and filling it with a precursor of an electrochromic material;

[0018] 2) After the film is dried, it is calcined at a high temperature to obtain H-inorganic oxide / electrochromic material PCs.

[0019] According to the above technical solution, preferably, in step 1), the conductive base is a conductive substrate selected from the group consisting of ITO and FTO, or two or more thereof.

[0020] According to the above technical solution, preferably, in step 1), the precursor of the electrochromic material is one or more of peroxytungstic acid, ammonium metatungstate, tungsten phosphate, ammonium metavanadate, vanadic acid, sodium vanadate, nickel chloride, nickel sulfamate, and nickel carbonate.

[0021] According to the above technical solution, preferably, in step 1), the raw material of the inorganic oxide is one or more of tetraethyl orthosilicate, manganese carbonate, and zirconium oxychloride octahydrate.

[0022] According to the above technical solution, preferably, in step 1), the concentration of the ethanol dispersion of the inorganic oxide-coated polymer microspheres is 5-10 wt %, and the concentration of the precursor solution of the electrochromic material is 5-10 wt %.

[0023] According to the above technical solution, in a preferred case, step 1) is specifically as follows: coating an ethanol dispersion of inorganic oxide-coated polymer microspheres on a conductive substrate, and then immersing the conductive substrate in a solution of a precursor of an electrochromic material and taking it out after 1-2 seconds.

[0024] According to the above technical solution, preferably, in step 2), the coating amount of the dispersion is about 20 μL / cm 2 .

[0025] According to the above technical solution, preferably, in step 2), the high temperature calcination temperature is 300-400° C. and the time is 5-7 hours.

[0026] According to the above technical solution, preferably, it also includes 3) using an aqueous solution of lithium salt as an electrolyte, connecting the film obtained in step 2) to a circuit, and realizing an electrochromic photonic crystal material with repeatable color change by switching the direction of the electric field.

[0027] According to the above technical solution, preferably, in step 3), the lithium salt used is one or more of lithium carbonate, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate and lithium hexafluorophosphate.

[0028] According to the above technical solution, preferably, in step 3), the concentration of the aqueous solution of the lithium salt is 0.1-1 mol / L.

[0029] According to the above technical solution, preferably, in step 3), the voltage is 1 to 5V.

[0030] According to the above technical solution, in the preferred case, step 3) is specifically as follows: using an aqueous solution of 0.1-1 mol / L lithium salt as the electrolysis environment, connecting the film to the circuit and applying a voltage of 1-5 V, and the color of the film changes after 5 seconds; switching the power direction, the color change of the film is restored.

[0031] The beneficial effects of the present invention are:

[0032] The present invention provides a composite photonic crystal film (H-inorganic oxide / electrochromic material PCs) of an opal photonic crystal structure support skeleton composed of hollow nano-microspheres of inorganic oxides and an electrochromic material of an inverse opal structure in the gaps of the skeleton. The unique internal support skeleton structure of the film can greatly improve its color quality and microscopic morphology, and the film can change color by regulating the shell thickness of the hollow nano-microspheres and the electric field, respectively, and has the ability to quickly respond to color change under an external electric field. The electrochromic photonic crystal film of this structure has many advantages such as rich colors, high color quality, stable and repeatable color change effect, and has good application prospects in the field of electronic display. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The SEM images of H-inorganic oxide / electrochromic material PCs prepared from inorganic oxide hollow nanospheres with different shell thicknesses; a) hollow nanosphere cavity diameter = 240nm, shell thickness 29nm; b) hollow nanosphere cavity diameter = 240nm, shell thickness 19nm; c) hollow nanosphere cavity diameter = 240nm, shell thickness 60nm. a) The H-inorganic oxide / electrochromic material PCs are prepared in Example 1; b) The H-inorganic oxide / electrochromic material PCs are prepared in Example 2; c) The H-inorganic oxide / electrochromic material PCs are prepared in Example 3.

[0034] Figure 2 The images of the electrical response reflection spectrum shift of H-inorganic oxide / electrochromic material PCs prepared from hollow nanospheres of inorganic oxide with different shell thicknesses are shown below: a) yellow-green change, hollow nanosphere cavity diameter = 240nm, shell thickness 29nm; b) cyan change, hollow nanosphere cavity diameter = 240nm, shell thickness 19nm; c) red-green change, hollow nanosphere cavity diameter = 240nm, shell thickness 60nm. a) The H-inorganic oxide / electrochromic material PCs are prepared in Example 1; b) The H-inorganic oxide / electrochromic material PCs are prepared in Example 2; c) The H-inorganic oxide / electrochromic material PCs are prepared in Example 3.

[0035] Figure 3 The graphs are the cycle performance test graphs of the electrochromic film described in Example 27, and the sample used is the sample described in Example 1. a) Voltage reciprocating change image; b) Current reciprocating change image; c) Film reflection intensity reciprocating change image.

[0036] Figure 4Reflection spectra of H-inorganic oxide / electrochromic material PCs film without / with inorganic oxide hollow nanospheres embedded in inverse opal electrochromic material. DETAILED DESCRIPTION

[0037] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0038] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are commercially available or can be prepared by conventional methods unless otherwise specified.

[0039] Example 1

[0040] A yellow-green electrochromic photonic crystal film with a H-SiO2 / WO3 structure composed of SiO2 hollow nano-microspheres with a diameter of 240nm and a shell thickness of 29nm and an electrochromic material WO3, the specific preparation process is as follows:

[0041] The inorganic oxide shell raw material used was tetraethyl orthosilicate, and the required template microspheres were silica-coated polystyrene microspheres with a diameter of 240 nm and a shell thickness of 29 nm. At room temperature, 5 wt% of the ethanol dispersion of silica-coated polystyrene microspheres was coated on the FTO conductive substrate, and the coating amount of the dispersion was about 20 μL / cm 2 The conductive substrate is then immersed in a 5wt% aqueous solution of peroxytungstic acid, a precursor of WO3, for 1-2s and taken out. After high-temperature sintering at 300°C for 1h, a yellow-green electrochromic photonic crystal film with a H-SiO2 / WO3 structure having a diameter of 240nm and a shell thickness of 29nm is obtained.

[0042] Its microstructure is Figure 1 As shown in a, the initial reflection color of the structure is yellow. Using 0.1 mol / L lithium carbonate aqueous solution as the electrolysis environment, the film is connected to the circuit and a 1V voltage is applied. After 5 seconds, the color of the film changes from yellow to green. When the power-on direction is switched, the film changes from green to yellow. During the power-on process, the corresponding reflection peak has an electrical response displacement effect. The relevant spectrum is shown in Figure 2 As shown in a.

[0043] Example 2

[0044] A cyan-blue electrochromic photonic crystal film with a H-SiO2 / NiO structure composed of SiO2 hollow nano-microspheres with a diameter of 240nm and a shell thickness of 19nm and an electrochromic material NiO, the specific preparation process is as follows:

[0045] The inorganic oxide shell raw material used was tetraethyl orthosilicate, and the required template microspheres were silica-coated polystyrene microspheres with a diameter of 240 nm and a shell thickness of 19 nm. At room temperature, a 10 wt % silica-coated polystyrene ethanol solution was coated on the FTO conductive substrate, and the coating amount of the dispersion was about 20 μL / cm 2 The conductive substrate was immersed in a 10wt% aqueous solution of nickel carbonate, a precursor of NiO, for 1-2s and then taken out. After high-temperature sintering at 500°C for 1h, a cyan-changing electrochromic film with a composite inverse opal photonic crystal structure formed by hollow nano-microsphere shells with a diameter of 240nm and a shell thickness of 19nm embedded in the pores of the NiO inverse opal skeleton structure was obtained.

[0046] Its microstructure is Figure 1 As shown in b, the initial reflection color of the structure is cyan. Using 0.1 mol / L lithium carbonate aqueous solution as the electrolysis environment, the film is connected to the circuit and a 5V voltage is applied. After 5s, the color of the film changes from cyan to blue. When the power-on direction is switched, the film changes from blue to cyan. During the power-on process, the corresponding reflection peak has an electrical response displacement effect. The relevant spectrum is shown in Figure 2 As shown in b.

[0047] Example 3

[0048] A red-green electrochromic photonic crystal film with a H-SiO2 / V2O5 structure composed of SiO2 hollow nano-microspheres with a diameter of 240nm and a shell thickness of 60nm and an electrochromic material V2O5, the specific preparation process is as follows:

[0049] The inorganic oxide shell raw material used was tetraethyl orthosilicate, and the required template microspheres were silica-coated polystyrene microspheres with a diameter of 240 nm and a shell thickness of 60 nm. At room temperature, 5 wt% of the ethanol dispersion of silica-coated polystyrene microspheres was coated on the FTO conductive substrate, and the coating amount of the dispersion was about 20 μL / cm 2 The conductive substrate was immersed in a 5wt% aqueous solution of ammonium metavanadate, a precursor of V2O5. After high-temperature sintering at 200°C for 2h, a red-green changing electrochromic film with a composite inverse opal photonic crystal structure formed by hollow nano-microsphere shells with a diameter of 240nm and a shell thickness of 60nm embedded in the pores of the V2O5 inverse opal skeleton structure was obtained.

[0050] Its microstructure is Figure 1 -c, the initial reflection color of the structure is red, using Li +The film was connected to the circuit and a 2V voltage was applied for 5s. The film color changed from red to green. When the power-on direction was switched, the film changed from green to red. During the power-on process, the corresponding reflection peak had an electrical response displacement effect. The relevant spectrum is shown in the figure below. Figure 2 -c.

[0051] Embodiments 4 to 6

[0052] By changing the shell thickness of the hollow nano-microspheres used in Example 1 to 5nm, 16nm, and 35nm, respectively, blue-purple conversion, green-cyan conversion, and red-orange conversion composite inverse opal photonic crystal electrochromic films formed by tightly packed hollow nano-microspheres embedded in the pores of the WO3 inverse opal skeleton structure can be obtained.

[0053] Embodiments 7 to 9

[0054] By changing the shell thickness of the hollow nano-microspheres used in Example 2 to 10nm, 26nm, and 45nm, respectively, blue-purple conversion, yellow-green conversion, and red-orange conversion composite inverse opal photonic crystal electrochromic films formed by tightly packed hollow nano-microspheres nested in the pores of the NiO inverse opal skeleton structure can be obtained.

[0055] Embodiments 10 to 12

[0056] By changing the shell thickness of the hollow nano-microspheres used in Example 3 to 20nm, 36nm, and 42nm, respectively, blue-purple conversion, green-cyan conversion, and yellow-green conversion composite inverse opal photonic crystal electrochromic films formed by tightly stacked hollow nano-microspheres nested in the pores of the V2O5 inverse opal skeleton structure can be obtained.

[0057] Embodiments 13-14

[0058] The inorganic oxide shell raw materials used in Examples 1 and 4 to 6 are replaced by manganese carbonate and zirconium oxychloride octahydrate, respectively, and the corresponding silica shells are replaced by MnO2 and ZrO2, respectively, and colorful electrochromic films with a composite inverse opal photonic crystal structure formed by tightly stacked hollow nanospheres embedded in the pores of the WO3 inverse opal skeleton structure can be obtained.

[0059] Embodiments 15-16

[0060] The inorganic oxide shell raw materials used in Examples 2 and 7 to 9 are replaced by manganese carbonate and zirconium oxychloride octahydrate, respectively, and the corresponding silica shells are replaced by MnO2 and ZrO2, respectively, and colorful electrochromic films with a composite inverse opal photonic crystal structure formed by tightly stacked hollow nanospheres embedded in the pores of the NiO inverse opal skeleton structure can be obtained.

[0061] Embodiments 17-18

[0062] The inorganic oxide shell raw materials used in Examples 3 and 10 to 12 are replaced by manganese carbonate and zirconium oxychloride octahydrate, respectively, and the corresponding silica shells are replaced by MnO2 and ZrO2, respectively, and colorful electrochromic films with a composite inverse opal photonic crystal structure formed by tightly stacked hollow nanospheres embedded in the pores of the V2O5 inverse opal skeleton structure can be obtained.

[0063] Embodiments 19 to 20

[0064] The silica-coated polystyrene microspheres described in Example 1 were replaced by silica-coated polymethyl methacrylate and silica-coated poly(styrene-methyl methacrylate-acrylic acid), respectively, to obtain a yellow-green changing electrochromic film with a composite inverse opal photonic crystal structure formed by hollow nano-microsphere shells with a diameter of 240±5nm and a shell thickness of 29nm embedded in the pores of a WO3 inverse opal skeleton structure.

[0065] Examples 21-22

[0066] By replacing the precursors described in Example 1 with ammonium metatungstate and tungsten phosphate, respectively, a yellow-green electrochromic film having a composite inverse opal photonic crystal structure formed by tightly packed hollow nanospheres embedded in the pores of the WO3 inverse opal skeleton structure can be obtained.

[0067] Embodiments 23-24

[0068] By replacing the precursors described in Example 2 with vanadic acid and sodium vanadate, respectively, a cyan-changing electrochromic film with a composite inverse opal photonic crystal structure formed by tightly stacked hollow nanospheres embedded in the pores of the V2O5 inverse opal skeleton structure can be obtained.

[0069] Embodiments 25-26

[0070] By replacing the precursors described in Example 3 with nickel chloride and nickel sulfamate, respectively, a red-green electrochromic film having a composite inverse opal photonic crystal structure formed by tightly packed hollow nano-microspheres embedded in the pores of the NiO inverse opal skeleton structure can be obtained.

[0071] Embodiment 27

[0072] The sample (electrochromic photonic crystal film) described in Example 1 was subjected to a cyclic response test under the electrochromic test conditions. The test results are as follows: Figure 3 As shown in a and b), as the voltage and current change, the reflection peak intensity of the sample has the performance of cyclic reciprocating shift, which indicates that the film has good cyclic performance.

[0073] Embodiments 28 to 32

[0074] By replacing the lithium salt in the electrolyte described in Example 1 with lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate and lithium hexafluorophosphate, respectively, a yellow-green changing electrochromic film with a composite inverse opal photonic crystal structure formed by hollow nano-microsphere shells with a diameter of 240±5nm and a shell thickness of 29nm embedded in the pores of a WO3 inverse opal skeleton structure can be obtained.

[0075] Comparative Example 1

[0076] A tungsten trioxide inverse opal photonic crystal structure electrochromic film without hollow nanospheres embedded. The template microspheres described in Example 1 are replaced with polystyrene microspheres, and the preparation is carried out according to the method of Example 1 to obtain an electrochromic film with an inverse opal photonic crystal structure formed only by a WO3 inverse opal skeleton structure. Its reflection spectrum is as follows Figure 4 As shown, compared with the reflection spectrum of Example 1, the relative intensity of the sample in Comparative Example 1 is greatly reduced.

Claims

1. A colorful photonic crystal film structure capable of repeated electrochromic change, characterized in that: The structure of the colorful photonic crystal film capable of repeated electrochromism is: an opal photonic crystal structure composed of hollow nano-microspheres of inorganic oxides is used as a supporting skeleton, and an inverse opal structure electrochromic material is filled in the gaps of the skeleton to form a composite photonic crystal film of hollow nano-microspheres-electrochromic material; The micro-nano structure of the film is a tightly packed multi-cavity structure; the hollow inorganic oxide nanospheres have an air core-inorganic oxide shell structure, the diameter of the microspheres is 200-400nm, and the thickness of the inorganic oxide shell layer is 5-60nm.

2. The multi-colored photonic crystal film structure capable of repeated electrochromism according to claim 1, characterized in that: The shell material of the inorganic oxide hollow nano-microspheres is one or two of SiO2, MnO2 and ZrO2.

3. The multi-colored photonic crystal film structure capable of repeated electrochromism according to claim 1, characterized in that: The electrochromic material is one or two of WO3, V2O5 and NiO.

4. The multi-colored photonic crystal film structure capable of repeated electrochromism according to claim 1, characterized in that: The inorganic oxide hollow nano-microspheres are formed by removing the polymer from the inorganic oxide shell-coated polymer core microspheres in a heat treatment step.

5. The multi-colored photonic crystal film structure capable of repeated electrochromism according to claim 4, characterized in that: The polymer core is one or more of polystyrene, polymethyl methacrylate, and poly(styrene-methyl methacrylate-acrylic acid).

6. The method for preparing a colorful photonic crystal thin film structure capable of repeated electrochromism according to any one of claims 1 to 5, characterized in that: The steps include: 1) constructing an opal photonic crystal composed of inorganic oxide-coated polymer microspheres on a conductive substrate as a precursor template of a hollow nano-microsphere photonic crystal, and filling it with a precursor of an electrochromic material; 2) After the film is dried, it is calcined at high temperature to obtain an electrochromic photonic crystal film.

7. The preparation method according to claim 6, characterized in that: The conductive substrate is one or more of ITO and FTO; the precursor of the electrochromic material is one or more of peroxytungstic acid, ammonium metatungstate, tungsten phosphate, ammonium metavanadate, vanadic acid, sodium vanadate, nickel chloride, nickel sulfamate, and nickel carbonate; the raw material of the inorganic oxide is one or more of tetraethyl orthosilicate, manganese carbonate, and zirconium oxychloride octahydrate; the concentration of the ethanol dispersion of the inorganic oxide-coated polymer microspheres is 5-10wt%, and the concentration of the precursor solution of the electrochromic material is 5-10wt%; the temperature of the high-temperature roasting is 300-400°C, and the time is 5-7h.

8. The preparation method according to claim 6, characterized in that: Step 1) specifically comprises: coating an ethanol dispersion of inorganic oxide-coated polymer microspheres on a conductive substrate, and then immersing the conductive substrate in a solution of a precursor of an electrochromic material for 1-2 seconds and then taking it out.

9. The preparation method according to claim 6, characterized in that: The method further comprises 3) using an aqueous solution of lithium salt as an electrolyte, connecting the film obtained in step 2) to a circuit, and realizing electrochromism of the photonic crystal film by switching the direction of the electric field.

10. The preparation method according to claim 9, characterized in that: The concentration of the aqueous solution of lithium salt is 0.1-1 mol / L, and the voltage is 1-5V.

Citation Information

Patent Citations

  • Preparation method of electrochromic film having photonic crystal structure

    CN102978674A

  • Prussian blue composite photonic crystal and preparing method and application thereof

    CN105384176A